2010
DOI: 10.1158/0008-5472.can-09-4480
|View full text |Cite
|
Sign up to set email alerts
|

4-1BB Ligand as an Effective Multifunctional Immunomodulator and Antigen Delivery Vehicle for the Development of Therapeutic Cancer Vaccines

Abstract: Therapeutic subunit vaccines based on tumor-associated antigens (TAA) represent an attractive approach for the treatment of cancer. However, poor immunogenicity of TAAs requires potent adjuvants for therapeutic efficacy. We recently proposed the tumor necrosis factor family costimulatory ligands as potential adjuvants for therapeutic vaccines and, hence, generated a soluble form of 4-1BBL chimeric with streptavidin (SA-4-1BBL) that has pleiotropic effects on cells of innate, adaptive, and regulatory immunity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 49 publications
9
95
0
Order By: Relevance
“…In further support by the Winn assay (47), we observed that anti-CD137 mAb following cetuximab treatment enhanced adaptive immunity with a significantly higher rate of CD8 + T cell-mediated protection to EGFR-expressing and nonexpressing tumors. The role of adaptive immunity and CD8 + T cells may be an on-target effect of anti-CD137 mAbs in vivo influencing the function of multiple cell types including hematopoietic cells such as granulocytes, T cells, B cells, DCs, and monocytes in addition to NK cells, as well as nonhematopoietic cells (31,(48)(49)(50)(51). Recently, Lee et al reported that tumor-targeting mAbs such as cetuximab induce an adaptive tumor antigen-specific T cell response that is primed by NK cell activation and subsequent NK cell-DC crosstalk (20).…”
Section: Figurementioning
confidence: 99%
“…In further support by the Winn assay (47), we observed that anti-CD137 mAb following cetuximab treatment enhanced adaptive immunity with a significantly higher rate of CD8 + T cell-mediated protection to EGFR-expressing and nonexpressing tumors. The role of adaptive immunity and CD8 + T cells may be an on-target effect of anti-CD137 mAbs in vivo influencing the function of multiple cell types including hematopoietic cells such as granulocytes, T cells, B cells, DCs, and monocytes in addition to NK cells, as well as nonhematopoietic cells (31,(48)(49)(50)(51). Recently, Lee et al reported that tumor-targeting mAbs such as cetuximab induce an adaptive tumor antigen-specific T cell response that is primed by NK cell activation and subsequent NK cell-DC crosstalk (20).…”
Section: Figurementioning
confidence: 99%
“…The nu/nu and SCID mice are both competent in NK cells and macrophages and complement but lack a functional adaptive immune response. However, mAbs targeting CD137 in vivo likely influence the function of multiple cell types, including hematopoietic cells such as granulocytes, T cells, B cells, dendritic cells, and monocytes, in addition to NK cells, as well as nonhematopoietic cells (25,(40)(41)(42)(43). In particular, our partially immunodeficient mouse models do not explore the impact of trastuzumab and anti-CD137 combination therapy on the adaptive immune response.…”
Section: Figurementioning
confidence: 99%
“…4-1BBL is a newly discovered costimulatory molecule expressed on the surface of antigen-presenting cells. 4-1BBL belongs to the TNF ligand superfamily, and can bind to 4-1BB molecules on the surface of T cells, generating costimulatory signals for late immune response, which is critical for survival and response of the CD8 + T cell mass (Sharma et al, 2010). This pair of co-stimulatory molecules play an important role in the immune response, immunomodulation, and anti-tumor and viral infection defense, in transplant rejection, etc., and have become an important area of modern immunological research.…”
Section: Discussionmentioning
confidence: 99%